THM-coupled numerical analysis of temperature and groundwater level in-situ measurements in artificial ground freezing - A. Kostina; M. Zhelnin; O. Plekhov; K.A. Agutin (Fracture and Structural Integrity)
Belarusian Potash salt deposits are bedded under aquifers and unstable soil layers. Therefore, to develop the deposits a vertical mine shaft sinking is performed using the artificial ground freezing technology. Nowadays, real-time observations of ground temperature and groundwater level is applied to control the ground freezing process. Numerical simulation can be used for a comprehensive analysis of measurements results. In this paper, a thermo-hydro-mechanical model of freezing for water-saturated soil is proposed. The governing equations of the model are based on balance laws for mass, energy and momentum for a fully saturated porous media. Clausius-Clayperon equation and poroelastic constitutive relations are adopted to describe coupled processes in water and ice pore pressure, porosity and a stress-strain state of freezing soil. The proposed model was used to predict equivalent water content measured in Mizoguchis test and frost heave in a one-sided freezing test. Numerical simulation of ground freezing in the Petrikov mining complex located in Belarus has shown that the model is able to describe field measurements of pore pressure inside a forming frozen wall. Furthermore, the mismatch between hydro- and thermo-monitoring data obtained during the artificial freezing is analyzed.